INTERNAL AND EXTERNAL FACTORS OF MSME CREDIT GROWTH IN INDONESIA : A MARKOV SWITCHING APPROACH - Nailir Rohmah; Deky Aji Suseno (Jurnal REP (Riset Ekonomi Pembangunan), 2025)
MSME Credit Growth in Indonesia experienced a downward and upward trend during the period 2017 - 2024. This study aims to determine the effect of internal factors Non Performing Loan (NPL), Return on Asset (ROA), and Capital Adequacy Ratio (CAR) as well as external factors BI Rate, Inflation, and Exchange Rate on MSME credit growth in Indonesia. This study uses the Markov Switching approach to capture changes in the dynamics of MSME credit growth in various credit growth conditions. The results of this study indicate that in high credit growth conditions, MSME credit is positively influenced by BI Rate, Exchange Rate, and Capital Adequacy Ratio (CAR) and is negatively influenced by Inflation, Non Performing Loan (NPL), and Return on Asset (ROA) to MSME credit growth in Indonesia. However, in conditions of declining credit growth, MSME credit is only positively influenced by inflation and ROA to MSME credit growth in Indonesia. This study illustrates that the factors that influence MSME credit growth in various conditions are different. These findings can be used as a basis in formulating policies in various conditions of credit growth.